A broadband radar cross section reduction metasurface based on integrated polarization conversion and scattering cancelation. Issue 2 (29th November 2019) - Fang, Wei; Xie, Xianyou; Sun, Shining; Wang, Yingjie; Fan, Digang; Liu, Xiaochun; Chen, Ping
Abstract: In this paper, we proposed and demonstrated a broadband radar cross section (RCS) reduction metasurface by integrating polarization conversion and scattering cancelation. A broadband polarization conversion structure was designed based on split concentric ring. We used a 4 × 4 array of split ring structure and its mirror‐symmetric structure as the super‐cell units to construct a metasurface with chessboard structure. The metasurface can efficiently reduce the co‐polarization RCS for all azimuth angles of incident wave. The metasurface sample with optimized structure parameters was fabricated and measured. The measured 10 dB RCS reduction band of the metasurface is from 8.6 to 17.7 GHz.